2020
DOI: 10.1039/d0nr06060g
|View full text |Cite
|
Sign up to set email alerts
|

A parallel and cascade control system: magnetofection of miR125b for synergistic tumor-association macrophage polarization regulation and tumor cell suppression in breast cancer treatment

Abstract: Polarization regulation of tumor-association macrophages (TAMs) is a promising treatment method of tumor, while aiming at TAMs alone shows unsatisfactory therapeutic efficiency. Therefore, we design a parallel and cascade control...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…Generally, there are classically activated (M1) and alternatively activated (M2) macrophages, which exhibit distinct physiological functions and are characterized by specific markers such as CD86 and CD206, respectively. 48,49 As observed through the CLSM, the expression of CD86 was significantly upregulated on the BGNs-Man/Ag treated macrophages, which also exhibited a more spread out and irregular cell morphology, indicating the M1 polarization. 50 However, macrophages in the other groups still retained the round shape with negligible expression of CD86 on the cell membrane (Fig.…”
Section: Bgns-man/ag Activate the Autonomous Defence Of Macrophagesmentioning
confidence: 99%
“…Generally, there are classically activated (M1) and alternatively activated (M2) macrophages, which exhibit distinct physiological functions and are characterized by specific markers such as CD86 and CD206, respectively. 48,49 As observed through the CLSM, the expression of CD86 was significantly upregulated on the BGNs-Man/Ag treated macrophages, which also exhibited a more spread out and irregular cell morphology, indicating the M1 polarization. 50 However, macrophages in the other groups still retained the round shape with negligible expression of CD86 on the cell membrane (Fig.…”
Section: Bgns-man/ag Activate the Autonomous Defence Of Macrophagesmentioning
confidence: 99%
“…Results showed tumor weight reduction of 60% and tumor metastasis suppression of 50%. 153 Similarly, magnetic NPs were used for efficient transfection of microRNA-374a in glioma stem cells. 154 A combination of cationic lipid N,N -di- n -hexadecyl- N,N -dihydroxyethyl ammonium chloride formulated with co-lipid cholesterol together with magnetic NPs was used to enhance DNA uptake by human glioblastoma-astrocytoma, epithelial-like cell line, hepatocellular carcinoma, cervical cancer, and breast cancer cells, where enhanced transfection was observed after applying the magnetic field.…”
Section: Extrinsic-activationmentioning
confidence: 99%
“…-NPs conjugated to ligands that is targeted to bind molecules found in tumor cells in higher concentration than in normal cells Tf, TfR, 60,61 EGFR, 62,63 PSMA, 64,65 FR, 66,67 HER2, 69,70 ER, 71 CD-44, 72,73 Integrin, 74,75 Biotin receptor, 76 LHRH receptor, 77 lectin 78,79 , GSH [80][81][82] Ultrasound activation -mRNA-lipoplexes bound to microbubbles 123 -Nanobubbles composed of NPs enclosing gas is stabilized within a single cavity of nano-cups or nano-cone 124 -Nanosized lipid droplets 125 -Barium titanate as a piezoelectric NP 129 Magnetic field activation -Biodegradable dendritic silica NPs encapsulating glucose oxidase and Fe 3 O 4 NPs 141 -Anticancer drugs conjugated with magnetic NPs 142,143,145 -Magnetite particles used as a pore blocking 150 -Cationic lipopeptides and anionic magnetic NPs system in magnetofection 153,155 Light activation/Photodynamic therapy -Near infrared 161,162 -Visible light 163,164 -X-ray 165 (Continued) https://doi.org/10.2147/IJN.S386037…”
Section: Concentration Dependent Activationmentioning
confidence: 99%
“…These NPs promoted an increase in the synthesis of iNOS and a decrease in arginase-1 promoting M1 macrophage polarization [ 111 ]. Other authors have used anionic magnetic NPs to transfect the same miR-125b and also observed M1 macrophage polarization in an orthotopic mouse model of breast cancer [ 112 ].…”
Section: Nanoparticles To Target and Treat Tumour-associated Macrophagesmentioning
confidence: 99%